A comparison of neonatal outcomes between adolescent and adult mothers in developed countries: A systematic review and meta-analysis. (April 2020) - Marvin-Dowle, Katie; Soltani, Hora
Abstract: Evidence suggests that adolescent pregnancies are at increased risk of adverse neonatal outcomes compared to adult pregnancies; however, there are significant inconsistencies in the literature, particularly in studies conducted in developed countries. The objective of this study therefore is to systematically review the current literature with regard to the relationship between adolescent pregnancy and neonatal outcomes. A literature search was conducted in eight electronic databases (AMED, ASSIA, Child Development and Adolescent Studies, CINAHL, Cochrane Library, Health Source: Nursing, Maternity and Infant Care, MEDLINE and Scopus. The reference lists of included studies were also hand searched. Studies were included if: they were conducted in countries with very high human development according to the United Nations Human Development Index; reported at least one comparison between adolescents (19 years or under) and adult mothers (20–34 years); and were published between January 1998 and March 2018. Studies were screened for inclusion and data extracted by one reviewer. A second reviewer independently reviewed a sub-set of studies. Disagreements were resolved by consensus. Meta-analysis was performed using RevMan 5.3 using crude counts reported in the included studies. Sub-group analyses of adolescents aged 17 and under and 18–19 were conducted. Pooled analysis of adjusted odds ratios was also undertaken in order to consider the effect of confounding factors. Meta-analysis effect estimates are reported as risk ratios (RR) and pooled association as adjusted odds ratios (aORs). Point estimates and 95% confidence intervals are presented. After removal of duplicates a total of 1791 articles were identified, of which 20 met the inclusion criteria. The results of the meta-analysis showed adolescents to have increased risk of all primary adverse outcomes investigated. Sub-group analysis suggests an increased risk of perinatal death and low birthweight for children born to adolescent mothers; 17 and under (perinatal death: RR 1.50, CI 1.32–1.71: low birthweight RR 1.43, CI 1.20–1.70); 18–19 (perinatal death RR 1.21, CI 1.06–1.37: low birthweight RR 1.10, CI 1.08–1.57). Mothers aged 17 and under were also at increased risk of preterm delivery (RR 1.64, CI 1.54–1.75). Analysis adjusted for confounders showed increased risk of preterm delivery (aOR 1.23, CI 1.09–1.38), very preterm delivery (aOR 1.22, CI 1.03–1.44) and neonatal death (aOR 1.31, CI 1.14–1.52). Findings show that young maternal age is a significant risk factor for adverse neonatal outcomes in developed countries. Adolescent maternal age therefore should be considered as a potential cause for concern in relation to neonatal health and it is recommended that health care professionals respond accordingly with increased support and monitoring.